Socio-cultural beliefs and perception of menopausal symptoms: A study in urban Indian women. - A Choudhary; P Choudhary (Asian Journal of Medical Research, 2013)
Objective of the exercise was to study and assess severity and the types of menopausal symptoms in perimenopausal women in urban India and to verify whether psycho-socio-cultural beliefs and attitudes influence the perception of menopausal symptoms. Methods: Subjects in this exercise were women between forty to sixty years of age. The tool used was a detailed questionnaire. Results :The results were assessed according to Menopause Rating System. Conclusion: Family centric Indian women consider menopause as a natural progression in life with minor nuisance value, self limiting symptoms and a life free from fear of pregnancy and inconvenience of menses. Unlike their western counter-parts, Indian women experience lesser symptoms with lesser severity, which do not merit treatment like HRT. Prevalent socio-cultural beliefs, attitudes towards menopause, family and self values in an Indian woman play a major part in her perception of menopause and its consequence. Key Words:, ,